Overview of fetomaternal outcome in twin gestation - Desai, Forum A.; Yadava, Pushpa A.; Jani, Shashwat K.; Mehta, Kush M.; Rawal, Dhwani R.; Patel, Dhruvi R.; Asudani, Nitya P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Twin pregnancy, involving the presence of two fetuses in the uterus, has intrigued humanity across history. Key challenges presented by twin pregnancies include prematurity, low birth weight (LBW), intrauterine growth restriction (IUGR), birth trauma, asphyxia, and congenital anomalies. Preterm delivery poses the most significant risk, contributing to elevated perinatal mortality, neonatal morbidity, and long-term health issues for twins. Methods: Retrospective study at Smt NHL Municipal Medical College analyzed 80 twin pregnancies from July 2022 to January 2024. Data included patient demographics, complications, and neonatal outcomes, informing findings through data analysis. Results: In this study, the majority were under 30 years old (56%) and primigravida (68%), with 48% having a BMI over 30. Common complications included preterm labor (70%), pregnancy-induced hypertension (27.5%), and gestational diabetes (20%). Most twin pregnancies were dichorionic diamniotic (80%). Caesarean section rate was 47.5%. Deliveries mostly occurred between 33-36 weeks gestation, with cephalic-cephalic presentation being most common (40%). Neonatal complications were primarily prematurity (50%), resulting in high NICU admissions (62%) and a neonatal death rate of 13.76%. Conclusions: Multiple pregnancies require early diagnosis and vigilant care to reduce maternal and perinatal risks. Access to skilled healthcare providers and advanced facilities is crucial. Antenatal care must be strengthened for timely referrals. Ultrasonography aids early complication detection. Further advancements and awareness are essential for improved outcomes.